Heart Condition in Convalescents of Hemorrhagic Fever with Renal Syndrome According to Echocardiography Data - K. M. Manakhov; O. E. Tsarenko; O. N. Chevplyanskaya; L. I. Bagautdinova; A. V. Melnikov; O. V. Malinin; M. V. Dudarev; D. S. Sarksyan; A. E. Platonov; V. V. Maleev (Столичная издательская компания, 2021)
Aim. To study the morpho-functional parameters of the heart in convalescents of hemorrhagic fever with renal syndrome (HFRS) using echocardiography.Material and methods. The study included 27 patients without any chronic diseases who had severe or moderate HFRS (the main group) within 3 weeks after their discharge from the infection diseases hospital. The reference group consisted of 19 patients comparable by age and gender, without any chronic diseases. Transthoracic echocardiography was the basic method of heart and hemodynamics investigation. The test was performed using tissue Doppler and non-Doppler assessment of left ventricle systolic deformation method (speckle-tracking method).Results. Violation of longitudinal systolic deformation of the left ventricle was observed in 15 (55.6%) patients, which was combined with diastolic left ventricle filling by the type of relaxation violation in 8 (29.6%) cases. Mitral valve insufficiency of 1 degree was identified in 11 (40.7%) HFRS patients, insufficiency of the tricuspid valve of 1 degree was identified in 4 (14.8%) patients. Pericardial effusion was detected in 2 (7.4%) patients. In 7 (25.9%) patients in the first 3 weeks after discharge from the hospital, additional floating echoes were detected on the leaves and fibrous ring of the aortic valve, which were considered as a manifestation of thromboendocarditis.Conclusion. Further investigation is necessary to assess the prognostic value (including the risk of thromboembolic complication developing) of the changes revealed in HFRS convalescents and to support the inclusion of echocardiography in the examination program during dispensary observation of HFRS-convalescents.